The Babesia observational antibody (BAOBAB) study: A cross-sectional evaluation of Babesia in two communities in Kilosa district, Tanzania. - Evan M Bloch; Zakayo Mrango; Mabula Kasubi; Jerusha Weaver; Aleksandra Mihailovic; Beatriz Munoz; Anna Weimer; Andrew Levin; Laura Tonnetti; Jeffrey M Linnen; Vanessa Brès; Douglas E Norris; et al. (Public Library of Science (PLoS), 2019)
Background Babesia, a tick-borne genus of intraerythrocytic parasites, is understudied in humans outside of established high-endemic areas. There is a paucity of data on Babesia in Africa, despite evidence that it is regionally present. A pilot study suggested that Babesia was present in a rural district of Tanzania. Methodology/principal findings A cross-sectional study was conducted July-August 2017: residents in a case hamlet that had clustering of subjects with high signal-to-cut off (S/CO) ratios for antibodies against B. microti in the pilot study, and a control hamlet that had lacked significant signal, were evaluated for B. microti. Subjects aged ≥15yrs (n = 299) underwent clinical evaluation and household inspections; 10ml whole blood was drawn for Babesia transcription mediated amplification (TMA), B. microti indirect fluorescent antibody testing (IFA) and rapid diagnostic testing (RDT) for Plasmodium spp. Subjects aged <15yrs (n = 266) underwent a RDT for Plasmodium and assessment by ELISA for B. microti antibodies. A total of 570 subjects participated (mean age 22 [<1 to 90yrs]) of whom 50.7% were female and 145 (25.5%) subjects were Plasmodium RDT positive (+). In those <15yrs, the median ELISA S/CO was 1.11 (IQR 0.80-1.48); the median S/CO in the case (n = 120) and control (n = 146) hamlets was 1.19 (IQR 0.81-1.48) and 1.06 (IQR 0.80-1.50) respectively (p = 0.4). Children ≥5yrs old were more likely to have a higher S/CO ratio than those <5yrs old (p<0.001). One hundred (38%) subjects <15yrs were Plasmodium RDT+. The median S/CO ratio (children <15yrs) did not differ by RDT status (p = 0.15). In subjects ≥15yrs, no molecular test was positive for Babesia, but four subjects (1.4%) were IFA reactive (two each at titers of 128 and 256). Conclusions/significance The findings offer further support for Babesia in rural Tanzania. However, low prevalence of seroreactivity questions its clinical significance.